A telephone reminder to enhance adherence to interventions in cardiovascular randomized trials: A protocol for a study within a trial (SWAT). Issue 1 (15th February 2020) - Bensaaud, Abdelsalam; Gibson, Irene; Jones, Jennifer; Flaherty, Gerard; Sultan, Sherif; Tawfick, Wael; Jordan, Fionnuala
Abstract: The impact of reduced adherence in randomized clinical trials is well documented in the literature. Nonadherence can negatively affect the trial sample size and estimation of the treatment effect. This protocol aims to evaluate the effects of a telephone call reminder on the adherence rates of participants to interventions in a cardiovascular randomized trial. This is a study within a trial (SWAT). The host trial is evaluating the effectiveness of a multidisciplinary 16‐wk cardiovascular disease prevention program on risk factor profile among patients with carotid artery stenosis. Simultaneously, this SWAT will evaluate the effectiveness of telephone call reminders on the participants' adherence to the host trial intervention. The primary outcome is adherence to the protocol of the host trial. Secondary outcomes are level of adherence, number of dropouts, and time to drop out from the host trial.